PENINGKATAN KAPASITAS APARATUR PEMERINTAH DESA KUTAJAYA - Rahmat Diffa Basri Ardana; Alfiana Indah Muslimah; Musyaffa Amin Ash Shabah (Universitas Islam 45 Bekasi, 2022)
The problems that exixt in the Kutajaya village government are that optimal administration has not been implemented, this can be seen in the incomplete population administration in kutajaya village and the issuance of decrees to community empowerment institutions and youth organizations. The method of implementation in the activity program is public education, a socialization seminar, in which the author collaborates with university education academics as resource persons to be able to provide material related to increasing the capacity of the village apparatus. With this socialization seminar, village officials can bring the knowledge provided by professional speakers in their fields. The results provided from the program are able to provide understanding to village officials regarding administration and community empowerment. It can be concluded that increasing the capacity of the village apparatus is very important for strengthening human resources in the village government. With efforts to increase the capacity of village government officials, it can bring human resources of village apparatus to optimize performance and be able to see the potential that exists in rural communities in kutajaya village. So it is very important for village officials to be able to improve their skills. Thus increasing the village government apparatus is an important part for the village government to be carried out by the village head as an effort to improve the skills pf the village apparatus.